Efeitos da incorporação de modelos de quebra e coalescência de bolhas em simulações multifásicas de processos de refino de aços - Carlos Eduardo Passagli Barral (2016)
The steelmaking involves several processes, where it is possible to identify a great variety of phenomena. These process has in his structure the interaction between gas in the form of bubbles and liquid steel. Furthermore, most studies using the fluid in these processes considers that the bubbles have a fixed diameter, excluding therefore the variation in their sizes, from breaking and coalescence of them. In one of the processes used in steelmaking ladles to homogenize chemically and thermally the steel called rinsing, it is observed that the size of the bubbles affects both the mixing time and in the capacity to flotation of the inclusions. It's possible to notice also that the production of special steels, with ultra-low carbon use vacuum refining process, having as one of its greatest representatives, RH degasser. In this sense, the high demand for ultra-low carbon steels requires improvements in the steel degassing process that can only achieve better results with the technological advancement in this reactor. In this case, is necessary to study the fundamental aspects of phenomena that govern it. In this work were carried out physical and mathematical modeling in the steelmaking ladle in order to understand the behavior of bubbles during this operation, using the study of mixing times curves, bubble size distribution profiles and the velocity of the bubbles profiles was obtained by physical and mathematical models. Were considered in this study two different models of break and coalescence of bubbles in the mathematical modeling, the multiple size groups (MUSIG) and dispersed diameters model (DDM). The mixing times (considering 95% mixture) obtained by the two models breaking and coalescence were very similar, but it was revealed that the inappropriate use of a fixed diameter in the modeling may result in significant deviations in the results. It was also noticed that although the average size of bubbles obtained by Musig and the DDM are similar, the variance presented by MUSIG is much smaller and differs from the behavior observed in the physical modeling, unlike DDM, which approached satisfactorily. Was evaluated the effect of the break and coalescence of bubbles in a vacuum degasser RH using the distribution profiles of bubble size and the construction of flow rate curves as a